McDowell e o Conteúdo da Experiência: entre o proposicional e o intuicional - Paulo Andrade Vitória (2015)
This dissertationpresents John McDowell's change of position regarding the content of perceptual experience in his paper Avoiding the Myth of the Given (2009). In the first chapter I presentthe thesis of propositionality developed by McDowell in his book Mind and World(2005). With the theory of propositional content McDowell seeks to engage the mind tothe world in a rational way, as well as overcome the oscillationbetween coherentism/Myth of the Given. In the second chapter, Ipresent the main objections made against McDowells position. I present the objections made by Travis,who led McDowell to revise his propositionality thesis.In the third chapter, I present the position developed in Avoiding the Myth of the Given(2009c)as a response to Travis.The dissertation tries to show that, in this paper, McDowell defends a view according to which perceptual experience has a conceptual but nonpropositional content, here named intuitional content. Iconcludewith an evaluationof this content in respect to epistemological problems.